Kefahaman Pelajar Akademi Pengajian Islam Universiti Malaya Terhadap Sifat 20: The Understanding of Students of Academy of Islamic Studies Universiti Malaya Towards Sifat 20 - Zainal Abidin, Mohd Syukri; Aznan, Nur Farah Nabihah; Abd. Latif, Faizuri (Jurnal Usuluddin, 2022)
Sifat 20 is part of the perfection sifat for Allah SWT who is infinite. It is obligatory to be known by every mukallaf along with detailed evidence. A correct knowledge and understanding of sifat 20 will confirm the obligation of worship and other benevolent deeds in addition to instilling nobility in behavior. However, with the influence of Western ideas and dogmas that are growing today as well as postmodern era, the understanding of society towards sifat 20 seems to be fading even among students with a background in Islamic studies. Therefore, this article will review the understanding of students of the Academy of Islamic Studies, Universiti Malaya (APIUM) towards sifat 20. This article uses a questionnaire survey that was distributed to 170 students from various fields of study and departments. The questionnaire was analyzed descriptively using SPSS software to see the results of the collected data. The results found that APIUM students have a positive understanding of sifat 20. However, this article also suggests that programs related to the study of Islamic creed, especially the study of sifat 20, continue to be actively implemented despite being in the millennium. A more efficient teaching approach should be applied to be compatible with the development of Industrial Revolution 4.0 (IR4.0).